TGF-β induces SOX2 expression in a time-dependent manner in human melanoma cells - Weina, Kasia; Novak, Daniel; Umansky, Viktor; Gebhardt, Christoffer; Utikal, Jochen (Pigment cell & melanoma research, 2016)
The sry-related high-mobility box (SOX)-2 protein has recently been proven to play a significant role in progression, metastasis, and clinical prognosis spanning several cancer types. Research on the role of SOX2 in melanoma is limited and currently little is known about the mechanistic function of this gene in this context. Here, we observed high expression of SOX2 in both human melanoma cell lines and primary melanomas in contrast to melanocytic nevi. This overexpression in melanoma can, in part, be explained by extra gene copy numbers of SOX2 in primary samples. Interestingly, we were able to induce SOX2 expression, mediated by SOX4, via TGF-β1 stimulation in a time-dependent manner. Moreover, the knockdown of SOX2 impaired TGF-β-induced invasiveness. This phenotype switch can be explained by SOX2-mediated cross talk between TGF-β and non-canonical Wnt signaling. Thus, we propose that SOX2 is involved in the critical TGF-β signaling pathway, which has been shown to correlate with melanoma aggressiveness and metastasis. In conclusion, we have identified a novel downstream factor of TGF-β signaling in melanoma, which may have further implications in the clinic.
Gesehen am 15.07.2019